Perfil del turista que visita la provincia de Pichincha en tiempos de pandemia. Año 2022 - Zumbana De La Cruz, Kimberly Zulay (2022)
The purpose of this degree work was to determine the profile of the tourist visiting the province of Pichincha in times of pandemic, a study that is within the type of transversal research, with a quantitative approach and descriptive scope. The research problem revolves around the pandemic caused by the covid-19 affecting the economy, health and freedom of tourists, which changed the need and travel preferences, in response, to know these changes the current research is presented which contains two specific objectives, For the first one, it was necessary to identify the total population of tourists who have entered the province in 2021, not having tourist income data updated by the competent entity, it was determined that the optimal formula to obtain the sample is the one that applies to infinite populations, obtaining as a response a total of 385 surveys. After obtaining the answer, we proceeded to the bibliographic review, mainly in documents issued by the MINTUR, as well as in its web page, with the motivation of selecting ten main tourist attractions that fulfilled tourist hierarchical characteristics of II, III, IV and have been determined as main destinations being these: La virgen del Panecillo, El Teleférico de Quito, La Basílica del Voto Nacional, Monumento a la Mitad del Mundo, Reserva Geobotánica Pululahua, Mindo, Refugio de Vida Silvestre Pasochoa, Cascadas del Río Pita, Pucara de Rumicucho and Reloj Solar Quitsato. With the information obtained, we proceeded to survey using the accidental sampling technique and making use of the data collection instrument, which has internal consistency and a questionnaire of 26 questions divided into the variables of demographic characterization, socioeconomic, motivation and preferences, The survey showed that 86% of the respondents were Ecuadorian, 41% were adults, 58% lived in Quito, 51% were women, 59% were single, 37% worked in the private sector, 30% earned a basic salary, 52% spent up to $100 per trip, 42% preferred nature tourism and 33% considered biosafety protocols important. For the second objective, a descriptive guide was designed, which covers the results obtained during the research. For its design, the use of two editing software, Illustrator and Freepik, was fundamental for the design of the front and back covers, characteristics of the province, index, information content, methodology, conclusions and recommendations